Evaluasi Pengembangan Pembelajaran Biologi Berbasis Media E-Learning pada Mahasiswa Tadris Biologi 3 Semester VI Universitas Islam Negeri Sumatera Utara - Oktariani, Puput; Furkonah Pasaribu, Kana; Khairunnisa, Azra; Amina, Siti; Melina Sari, Sri; Adiesty, Zahwa (IAI Nasional Laa Roiba Bogor, 2024)
The word learning is not far from a word, namely evaluation, along with the development of the times, and with the sophistication of existing technology, various kinds of media have emerged in the application of learning. E-Learning is the answer to all the sophistication that exists at this time. Where learning methods using technology are currently needed because of advances in technology in each place of learning, whether it's a school or college. This study uses the Research and Development method. The purpose of this study is to determine the development of E-Learning media-based learning. The results of the data that the researcher will obtain are the responses of Tadris Biology Students Semester 3 VI UINSU. Hopefully what is expected with this article can be an alternative choice or reference in conducting a study.